Sensibilidades e ambivalências em periódicos educacionais paulistas (1902-1911) - Santos, Tainã Maria Pinheiro dos (2018)
Education is one of the important issues relating to Republic in the first decades of the last century. This, especially in its school version, was an apparatus to lead the new generations for what it had become - or for what it wished to become - the nation, moving away from the imaginary and symbolic of the Second Empire. In order to do so, the republican education had its focus on guiding teachers not only to teach contents and methods, but inside and parallel to them, to improve the education of sensibilities of children and young people. One of the inversions in this experience are the pedagogical printed stuffs that, at a key moment in the press and in the school, carried out this impulse through the discursive structure composed especially of narratives, articles and prescriptions. Considering this framework, this thesis presents results of a research whose objective was to investigate topics of education of the sensibility in São Paulo in the first two decades of the twentieth century, which are substantially for the effort to produce sensitivities in accordance with the Republic. The research analyzed the Revista de Ensino da Associação Beneficente do Professorado Público Paulista and the Anuário de Ensino do Estado de São Paulo. It considered the myths in the form of reports, fictional or not; differentiated pedagogical orientations for boys and girls; the invention of a republican childhood, especially of scholarly character; the ambiguity of fantasies. The conclusions point out the strong gender division of prescriptions; the subjectivation of children and young people in school form, with emphasis on the processes of selfcontainment; the infantilization of the feminine, seen nature to be under social domination; the denegation of uncontrolled expressive forms, simultaneously with the valorization of the rituals of belonging to the Republic